Mengembangkan Kemasan Makanan yang Lebih Praktis melalui Inovasi Berbasis Kebutuhan Konsumen - Rita Febri Gistalia; Nela Amelia Maharani; Yoktan Andykha Olivier Seran; Tan Evan Tandiyono (Lembaga Pengembangan Kinerja Dosen, 2026)
The growth of the food industry encourages companies to continuously develop innovations that meet consumer needs, including product packaging. This study aims to develop an innovative food packaging concept based on consumer needs using a qualitative approach. The research was conducted at Universitas 17 Agustus 1945 Surabaya and involved three university students selected through purposive sampling. Data were collected through an initial survey, in-depth interviews, and a Focus Group Discussion (FGD). The survey results indicated that participants needed a more practical packaging solution for storing leftover snacks without requiring additional containers. The interview findings revealed that consumers preferred packaging that was convenient to use because transferring leftover food into separate containers was considered inconvenient. The initial concept of a resealable sticker packaging was then evaluated through the FGD. The discussion revealed that the concept was not sufficiently effective in maintaining product quality, leading to the development of a vacuum resealable packaging concept. This innovation was considered more effective in preserving product freshness, reducing air exposure, and providing greater convenience for consumers when storing leftover snacks. The findings demonstrate that involving consumers in the innovation development process can generate solutions that better address market needs while adding value to the product.